Peran Dukungan Sosial dalam Meningkatkan Resiliensi Peserta Didik: Perspektif Psikologi Pendidikan Islam - Faiqotun Nisa; Salamah Salamah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Student resilience is an essential capacity for coping with academic, social, and psychological challenges in educational settings. One of the external factors that plays a significant role in fostering resilience is social support. This study aims to analyze the role of social support in enhancing student resilience from the perspective of Islamic educational psychology. This research employed a library research approach by reviewing and synthesizing relevant journal articles and scholarly books published between 2021 and 2025 related to social support, student resilience, and Islamic educational psychology. Data were analyzed using content analysis and thematic analysis of previous research findings. The results indicate that social support derived from family, teachers, peers, and the school environment functions as a protective factor that enhances students’ adaptive abilities, emotional regulation, and resilience in facing academic pressures. From the perspective of Islamic educational psychology, social support is integrated with Islamic values such as ukhuwah (brotherhood), ta’awun (mutual assistance), sabr (patience), and tawakkul (trust in God), which strengthen students’ resilience in a holistic manner, encompassing both psychological and spiritual dimensions. This study contributes theoretically to the development of Islamic educational psychology and provides practical implications for educational institutions in creating supportive and value-based learning environments.